PENGOLAHAN TALAS (Colocasia Esculenta L., Schott) MENJADI KERIPIK MENGGUNAKAN ALAT VACUM FRYING DENGAN VARIASI WAKTU - Iskandar, Haerul; Patang, Patang; Kadirman, Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2018)
Research this aim for knowing influence variation time frying chips of talas (Colocasia esculenta L ., Schott) use vacuum frying to organoleptic quality, moisture content, levels ash, content fat, protein and carbohydrates. The samples used were chips of talas of which were processed using vacuum frying at 90 0C with frying time of 65, 70 and 75 minutes, this study used a complete randomized design (RAL). Results research chips of talas use vacuum frying at a temperature of 90 0C with time frying 75 minutes is treatment best with produce water content (1.21%), levels ash (0.77%), protein (1.97%), fat (25.80%), carbohydrate (70.29%). The level Favorite ( hedonic ) the chips of talas on time frying 75 minutes use vacuum frying with temperature 90 0C is treatment most liked by the panelis both in terms of color, taste, aromaÂ  and texture.